Separating the hawks from the doves - Keith Henwood; Daniel Friedman; Ryan Oprea (University of California, Economics Department, 2009)
Human players in our laboratory experiment converge closely to the symmetric mixed Nash equilibrium when matched in a single population version of the standard Hawk-Dove game. When matched across two populations, the same players show clear movement towards an asymmetric (and very inequitable) pure Nash equilibrium of the same game. These findings support a distinctive prediction of evolutionary game theory.
Keywords: C73; C92; D74; 330; evolutionary dynamics; Hawk-Dove game; game theory; laboratory experiment; continuous time game; Dynamisches Spiel; Konflikt; Evolutionäre Spieltheorie; Test